Deference by submission. The Ecuadorian Constitutional Court and the abuse of the state of emergency (2021-2025) - Carbonell, María Helena (2025)
This research analyzes the actions of Ecuador’s Constitutional Court in supervising the states of emergency decreed between 2021 and 2025, a period in which 34 decrees were issued in response to social and security crises. It reveals that, in most cases, the Court has ensured compliance with formal requirements and has carried out rigorous substantive control to verify the actual existence of the facts and the proportionality of the measures. However, a tendency toward judicial deference to the executive branch has also been detected, which in some cases allows for the extension of measures without thorough review, posing risks to the effective protection of human rights and democracy. The importance of judicial oversight as a fundamental mechanism for preventing abuses and strengthening the constitutional rule of law in emergency contexts is highlighted, and it is emphasized as a key element in balancing security and rights in times of crisis. The research emphasizes the need for active and effective control to ensure that restrictions are justified, proportionate, and well-founded, thereby promoting a robust democracy even in exceptional situations.